Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12105-012-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Acantholytic Squamous Cell Carcinoma in Upper Aerodigestive Tract: Histopathology, Immunohistochemical Profile and Epithelial Mesenchymal Transition Phenotype Change

Abstract: Acantholytic squamous cell carcinoma is a rare variant of squamous cell carcinoma in the mucosa of upper aerodigestive tract. Histomorphologically, acantholytic squamous cell carcinoma may lose the typical features of conventional squamous cell carcinoma and mimic other epithelial or mesenchymal malignancies due to advanced acantholysis and dyskeratosis. Because of its rarity, information of prognosis, pathologic features and immunohistochemical profiles is limited. We have studied clinicopathologic features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
20
1
1
Order By: Relevance
“…Specifically, acantholytic squamous cell carcinoma (ASCC), also known as pseudoglandular carcinoma, is an uncommon histological variant of SCC (12,13) (7). In humans, this variant is rare, but it has been reported in the oral cavity (9,13), nasal cavity (1, 9), vulva (6), palate (9), maxilla (19), cecum (10) and breast (11). ASCC is also rare in animals, with only a few reports that have described ASCC in the mammary region (8) and oral cavity of dogs (4).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, acantholytic squamous cell carcinoma (ASCC), also known as pseudoglandular carcinoma, is an uncommon histological variant of SCC (12,13) (7). In humans, this variant is rare, but it has been reported in the oral cavity (9,13), nasal cavity (1, 9), vulva (6), palate (9), maxilla (19), cecum (10) and breast (11). ASCC is also rare in animals, with only a few reports that have described ASCC in the mammary region (8) and oral cavity of dogs (4).…”
Section: Introductionmentioning
confidence: 99%
“…carcinoma, basaloid squamous cell carcinoma, and ASCC, are well docu-mented and have prognostic significance. 5,6 This article documents the unique histomorphologic fea-tures in a case of oral epithelial dysplasia, which are reminiscent of those seen in ASCC. We have termed this unusual presentation adenoid dysplasia.…”
Section: Discussionmentioning
confidence: 94%
“…However, these features are evident throughout the tumor in cases of ASCC. 6,14,15 A recent study has found that increased vimentin expression within lesions of oral epithelial dysplasia closely correlates with histologic grade. This may represent a useful adjunct for the prediction of ma-lignant potential in high-risk lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Hasta sayılarının azlığı nedeniyle prognoz hakkında net yorum yapılamamakla birlikte akantolitik SHK alt tipinin daha agresif seyrettiği bilinmektedir. [1][2][3][4] Baş-boyun kanserli hastalarda uzak metastaz riski %4 ile %25 arasında değişmektedir. [5] Metastazlar hematojen yolla en sık akciğer (%60) ve kemiğe (%20) olmaktadır.…”
unclassified